A review of fundamentals, challenges, prospects, and emerging trends in hydrate-based desalination - Ali Jalili; Georgios Kolliopoulos (npj Clean Water)
Abstract Hydrate-based desalination (HBD) has emerged as a promising technology among conventional desalination methods due to its low energy consumption, wide operating window with regards to total dissolved solids (TDS), and efficient water recovery. This paper provides an in-depth review of the fundamental properties of hydrates, including thermodynamic and kinetic aspects of their formation. Then, it delves into recent advancements in thermodynamic and kinetic hydrate promoters that aim to address HBD’s main challenge, which is the slow hydrate formation process. Subsequently, the review systematically examines environmental and toxicity concerns associated with chemicals used in HBD, addressing the growing demand for sustainable and biodegradable desalination solutions. Finally, a comparative analysis between HBD and conventional methods highlights its potential as an energy-efficient and selective desalination process poised to enhance sustainability within the water-energy-environment nexus.